REFLECTIONS ON THE NOTION OF EXPERIENCE IN WALTER BENJAMIN'S WORKS - Sanches, Eduardo Oliveira; Silva, Divino Jose da [UNESP] (Univ Metodista Piracicaba-unimep, 2019)
The aim of this study is to analyze the notion of experience in the work of Walter Benjamin as a result of reflections carried out by the author on the theme from his youth to his maturity. Variations were shown on qualities of the concept of experience, which were gradually being built as the author shifted his focus from analysis and observation of social reality to talk of experience and modernity. In this way, Benjamin turned to knowledge as an exercise that evokes the event, the agoras, the senses of the aura. This conceptual dimension brings together the knowledge that is constituted from having experiences and not just doing them as modern science aims. Six trials were used to establish this analysis, they are: Experience (1913); On the program of the philosophy of the future (1918); Experience and Poverty (1933); The storyteller. Considerations on the work of Nicolai Leskov (1936); On some subjects in Baudelaire (1940) and Berliner Childhood: 1900 (written between 1926 and 1938).
Keywords: Experience; Modernity; Walter Benjamin